2022
DOI: 10.1002/ange.202112925
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating the Mechanisms of Action of Ferroptosis and the Photothermal Effect for Cancer Theranostics

Abstract: Combination therapy based on different mechanisms of cell death has shown promise in tumor therapy. However, when different modalities are integrated, the maximum synergy of the therapeutic effects is often lacking in the design. Herein, we report a cancer theranostic nanomedicine formula developed by considering the mechanisms of action of ferroptosis and the photothermal effect in combination therapy. The croconaine molecule was encapsulated as both a photothermal converter and an iron‐chelating agent with B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Besides, the FL intensity of TA probe also increased with prolonged laser irradiation time (Figure 2H), further confirming the heat‐augmented • OH generation of Fc‐CD NPs. Interestingly, the therapeutic efficiency of PTT was known to be restricted by thermoresistance arising from the expression of HSPs, 24,43 but it has been reported that upregulated ROS level was able to inhibit the HSPs expression 24,25 . Thus, the produced • OH could in turn overcome the inherent drawbacks of conventional PTT and result in multibenefit treatment outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the FL intensity of TA probe also increased with prolonged laser irradiation time (Figure 2H), further confirming the heat‐augmented • OH generation of Fc‐CD NPs. Interestingly, the therapeutic efficiency of PTT was known to be restricted by thermoresistance arising from the expression of HSPs, 24,43 but it has been reported that upregulated ROS level was able to inhibit the HSPs expression 24,25 . Thus, the produced • OH could in turn overcome the inherent drawbacks of conventional PTT and result in multibenefit treatment outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the therapeutic efficiency of PTT was known to be restricted by thermoresistance arising from the expression of HSPs, 24,43 but it has been reported that upregulated ROS level was able to inhibit the HSPs expression. 24,25 Thus, the produced • OH could in turn overcome the inherent drawbacks of conventional PTT and result in multibenefit treatment outcomes. Taken together, the synergistic heat and • OH generation capabilities of Fc-CD NPs were clearly confirmed, which are beneficial for achieving tumor-specific and enhanced synergistic therapy.…”
Section: Heat and • Oh Generation Capacities Of Fc-cd Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the PTT effect could amplify the Fenton reaction to form hydroxyl radicals and a labile iron pool. These cooperative effects constituted MR and PA imaging, ferroptosis, and PTT for cancer theranostics (Zeng et al, 2022). Chuang et al developed and used Y 2 O 3 :Eu@SiO 2 as a nanoscintillator for X-ray activated photodynamic therapy (PDT) in deep cancer theranostics.…”
Section: Theranostic Nanoparticlesmentioning
confidence: 99%
“…In this regard, HSPs was considered as the negative regulator of ferroptosis, and HSPs inhibition increases the efficiency of ferroptosis. It has been reported that the primary amines of HSPs could be cross-linked by ROS or LPO ending products [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%